Formulation And Characterization Of Nicardipine Hydrochloride Solid Dispersions And Oro dispersible Tablets Using Natural Seed Starch as Super disintegrant - Lakshmi, Battula Sowjanya; Sharma, Hariom; Vidyadhara, Suryadevara (Journal of Neonatal Surgery, 2025)
The current research aimed to improve the solubility and rate of dissolution of Nicardipine HCl, which is a drug that has low water solubility. This was achieved by utilizing solid dispersions and orodispersible tablets made from ESS4 (Entada scandens seed starch). The starches were extracted using water and alkali as solvents. The study evaluated the chemical composition and physical properties of seed starches. The solid dispersions were made utilizing a modified method of evaporating solvents with ESS4 as carrier in various amounts. Direct compression (DC) technique has been utilized in making tablets with optimized solid dispersions of Nicardipine HCl and various quantities of SSG (Sodium Starch Glycolate) along with CCS (Croscarmellose Sodium). Optimized solid dispersions as well as orodispersible tablets were also subjected for characterization including Scanning Electron Microscopy (SEM) and FTIR (Fourier Transform Infra-Red Spectroscopy). These findings indicated that ESS4 which was made using a 0.5% sodium hydroxide (ESS4). Demonstrated superior physicochemical characteristics compared to other starches. The solid dispersions made with ESS4 exhibited more drug release. The optimized dispersion NS4 was employed for the preparation of orodispersible tablets with CCS and SSG. The prepared tablets exhibited pre as well as post compression parameters within specified limits. The in-vitro drug release studies exhibited release of drugs more quickly. FTIR research demonstrated that there has been no drug-excipient interaction. Moreover, SEM images revealed nature of drug and excipients used. The study determined that the ESS4 has exceptional super disintegrant properties, indicating its potential application in developing an innovative formulation for the treatment of angina utilizing Nicardipine HCl